Left Inferior Frontal Gyrus Participates in Mediating the Renewal Effect Irrespective of Context Salience - Lissek, Silke; Klass, Anne; Tegenthoff, Martin (Frontiers in Behavioral Neuroscience, 2020)
The renewal effect of extinction demonstrates the context-dependency of extinction learning. It is defined as the recovery of an extinguished response occurring when the contexts of extinction and recall differ. Behavioral studies showed that modulating context relevance can strengthen context-specific responding. In our fMRI study, we investigated to what extent a modulation of context salience can alter renewal levels and provide additional information about the neural basis for renewal. In a within-subjects design, participants completed two sessions of an associative learning task in randomized order. In the salient condition (SAL), a context was presented alone at the start of each trial, before being presented together with the stimulus. The regular condition (REG) contained no context-alone phase. In about one third of participants (SWITCH), the context salience modulation significantly increased renewal rates in the SAL compared to the REG condition. The other participants showed either renewal (REN) or no renewal (NoREN) in both conditions. The modulation did not significantly affect learning performance during initial forming of associations or during extinction learning. In the SWITCH group, activation in left opercular inferior frontal gyrus (iFG) during the recall phase was associated with a renewal effect, together with activity in bilateral posterior hippocampus and ventromedial prefrontal cortex (vmPFC). Also during the extinction phase, left opercular iFG activation was higher in groups exhibiting renewal in recall, irrespective of the context salience modulation. Next to confirming participation of vmPFC in extinction recall, our findings provide novel insights regarding an as yet undetected, potentially important role for renewal-supporting processes in left iFG during extinction learning and recall, which are presumably based on the region’s proposed function of evaluating competing response options under conditions of ambiguity.